PUBLIC POLICY TOWARDS HIV MISCONCEPTIONS IN INDONESIA - Permadi, Agus; Aji, Aji (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2020)
This study focuses on HIV misconceptions in Indonesia. Based on Demographic and Health Surveys (DHS) Program, there are three common misconceptions about HIV: (1) whether HIV can be transmitted through mosquito bites, (2) whether transmission occurs by sharing food with a person who has HIV/AIDS, and (3) whether a healthy-looking person could have HIV. Using 2017 the Indonesia DHS, this study examines the impact of two factors - socio-demographic and media exposure - on HIV misconceptions in Indonesia. I found that respondents who belong to the younger age group, living in urban areas, have a higher degree of education, and have higher exposure to media were less likely to have misconceptions about HIV. This result indicates that to reduce HIV misconceptions in Indonesia, the government should make a targeted intervention program.